Tribocontact surface exploration after friction in hexanoic acid solution - E. G. Drogan; V. E. Burlakova (Advanced Engineering Research, 2019)
Introduction. The paper considers the evolution of friction coefficient of the pair of copper - steel alloy under friction in a hexanoic acid solution in various concentrations, and antiwear properties of the steel-steel friction pair in an oil-acidic medium. The work objective is to explore the effect of hexanoic acid additives on the tribological characteristics of friction pairs under the friction interaction in waterborne and paraffin-based formulations. Materials and Methods. Tribological studies of a brass-steel friction pair were carried out on the AE-5 end-type friction machine. Antiwear characteristics were explored on a four-ball friction machine (FBW) in accordance with the standard GOST 9490–75. When tested at the FBW, the objective parameters of the lubricity of the oiling compositions were: welding load (Рс); wear spot diameter (Dн), critical load (Рк). Roughness parameters of the servovite film were determined through the optical profilometry; its microgeometry and structure at the nanoscale – through the atomic force microscopy. Research Results. Tribological properties of the brass-steel tribocoupling in aqueous media and steel-steel one in petroleum paraffin-based media are studied. The dependence of the frictional characteristics of the brass-steel friction pair on the concentration of carboxylic acid is established. Its optimum concentration is specified, which provides the effect of wearlessness. A decrease in surface roughness is revealed as a result of the frictional interaction of a brass-steel friction pair in the hexanoic acid solution compared to the initial friction surface due to the formation of a sufficiently dense layer from fine-grained copper clusters with tight particle-size dispersion. The tribological characteristics of a steel-steel friction pair were found to depend on the composition of the lubricant. It is shown that the dependence of the size of the wear scar diameter (WSD) on the acid content in the base oil is nonmonotonic in nature with a pronounced minimum at a concentration of 0.1 mass. %. The critical load (Pк) at a content of 0.05 and 0.1 mass. % increases by 32%, welding load (Pc) - by 27%.Discussion and Conclusions. As a result of the tribological studies of a brass-steel friction pair in the hexanoic acid solution, it has been found that the optimum acid molar concentration in the lubricant composition is 0.1 mol/L. Under the frictional interaction of a brass-steel pair in the hexanoic acid solution, an antifriction copper film is formed on the friction surfaces, which contributes to a sharp decrease in the friction coefficient to 0.007 and metal wear of the friction pair to 25 times. As a result of the frictional interaction of a brasssteel friction pair in the hexanoic acid solution, a decrease in roughness is revealed compared to the initial friction surface. It is found that the frictional interaction of a brass-steel pair in the hexanoic acid solution causes a significant modification of the friction surface as a result of the deposition of finely dispersed copper clusters occurring in the lubricating medium composition and forming a servovite film. As a result of studies, it is found that the dependence of the WSD size on the acid content in the base oil is nonmonotonic in nature with a significant minimum at a concentration of 0.1 mass. %. It is shown that the addition of 0.1 mass. % of hexanoic acid into the lubricant composition exhibits the smallest wear of the steel-steel tribological pair, the WSD decreases to 0.497 mm, the critical load (Pк) and the welding load (Pc) increase by 32% and 27%, respectively.